Интерьер дома и изготовление мебели своими руками - Новоселов Ю. А. Юрий Александрович; Кулов А. С. Александр Сергеевич; Панкратов Е. С. Евгений Сергеевич (Б-ка сельского умельца)
Авт. указаны на обороте тит. л.